Cross Sectional Survey On Maxillo Facial Injuries In Road Traffic Accidents In Karachi - Tahira Hanif; Farah Ahmad; Ahsan Ashfaq; Syed Hasan Danish (ziauddin University, 2024)
Background: Injuries due to motorcycle accidents are frequent happenings in developing countries as people utilize it commonly as a mode of transport. In Pakistan 56% of Maxillofacial injuries can be associated to Road traffic accidents (RTA) majority of which are due to involvement of motorbikes. Methods: This cross sectional survey was carried out in public tertiary care setting in the year 2016. Three Hundred and Seventy participants were inducted in the study using Purposive sampling technique. Only those with maxillofacial injuries were included and diagnosed through conventional and panoramic radiographs and computed tomographic scans. Those who consented were included whereas, participants with language barrier or unable to answer were excluded. Data was collected by questionnaire with analysis being performed on SPSS version 21. Descriptive analysis was performed for quantitative variables with association between categorical variables tested through chi square. Bond of error was taken at 5% with 95% confidence interval. Permission was sought from ethical review board. Results: Majority, [267(84.5%)] were young patients with [ 282(89.2%)] patients involved in Motorcycle accidents. Of total participants male gender was [275(87%)] the driver inflicted in most situations [184(58.2%)]. Most patients [285(90.2%)] were without any safety device. Majority [220(69.6%)] had Mandibular fractures whereas, 111(35.1%) had Maxillary fractures. Soft tissue injuries were seen in 212(67.1%) patients. Conclusion: Motorcycle related accidents are common cause for maxillofacial injuries in road traffic accidents. Most patients suffered soft tissue injuries. Most commonly fractured bones were mandible and maxilla. Key Words: Maxillofacial injuries, Motorcycle, Accidents